SOME PROBLEMATIC ISSUES OF PREVENTING CRIMINAL OFFENSES IN THE ENVIRONMENTAL SPHERE IN UKRAINE (Bulletin of criminological association of Ukraine, 2025)
The most sensitive indicators of a society’s civilizational maturity are criminal offenses in the areas of environmental safety, environmental protection, and the misuse of budgetary funds. The growing trend of environmental crime in general, and crimes related to subsoil use at the expense of the state budget and the environment in particular, poses a significant challenge for Ukraine, especially under the conditions of martial law. By the way, it is the military illegal actions of the aggressor state — the Russian Federation — that have caused enormous damage to environmental safety and the environment, especially in the territories occupied by the enemy. Therefore, the issues of combating and preventing criminal offenses in the fields of subsoil use, environmental protection, and other types of natural resource exploitation — including through the misuse of budgetary funds — are highly relevant and require ongoing scientific attention. The misuse of public funds allocated by the state for environmental safety and protection by individuals vested with public authority contributes to reckless, corporatized commercialization, significant imitation of environmental and criminological policy, and a deepening of social injustice among members of society. Unfortunately, criminal statistics are replenished daily with cases of minor offenses, while the most dangerous criminal activities of financial-industrial and organized criminal groups in the environmental sphere remain largely beyond the reach of a highly politicized criminal justice system. Thus, environmental crime under the legal regime of martial law represents a highly profitable type of business within politico-economic criminal practices, and only law enforcement agencies are capable of counteracting it. Accordingly, in the course of our study on the prevention of criminal offenses in the environmental sphere, we employed a methodology aimed at understanding and addressing the problem through the use of criminal liability by law enforcement agencies for the misuse of state-allocated environmental protection funds. In addressing the prevention of criminal offenses in the environmental sphere, we hypothesized the practical need for a comprehensive, scientifically grounded study aimed at providing practical recommendations to law enforcement bodies regarding criminal-preventive activities in this field. The article notes that existing criminological research is substantial and distinguished by the depth of its scientific developments. However, it mostly pertains to general issues of preventing criminal offenses in the environmental domain. In order to harmonize national legislation with EU law, there is a need to introduce a series of amendments to the articles that establish criminal liability for environmental violations in Ukraine. Furthermore, it is necessary to address the issue of aligning criminal-legal norms aimed at ensuring environmental security with the corresponding administrative-legal regulations in the field of environmental protection.
Keywords: environmental safety; environmental crime; prevention; criminal offense; environment; budget funds; prosecution; police